Brain Organoids as Model Systems for Genetic Neurodevelopmental Disorders - Baldassari, Simona; Musante, Ilaria; Iacomino, Michele; Zara, Federico; Salpietro, Vincenzo; Scudieri, Paolo (Frontiers in Cell and Developmental Biology, 2020)
Neurodevelopmental disorders (NDDs) are a group of disorders in which the development of the central nervous system is disturbed. Such developmental brain dysfunction can manifest with different neurological and neuropsychiatric features including impaired motor function, learning, language or non-verbal communication. Frequent comorbidities include epilepsy and movement disorders. Advances in DNA sequencing technologies revealed identifiable genetic causes underlying an increasingly large proportion of NDDs, highlighting the need of experimental approaches to investigate the faulty genes and molecular pathways implicated in abnormal brain development. However, targeted approaches to investigate specific molecular defects and their implications in human brain dysfunction are prevented by limited access to patient-derived brain tissues. In this context, advances of both stem cell technologies and genome editing strategies during the last decade led to the generation of three-dimensional (3D) in vitro-models of cerebral organoids, holding the potential to recapitulate precise stages of human brain development with the aim of personalized diagnostic and therapeutic approaches. Recent progresses allowed to generate 3D-structures of both neuronal and non-neuronal cell types and develop either whole-brain or region-specific cerebral organoids in order to investigate in vitro key brain developmental processes, such as neuronal cell morphogenesis, migration and connectivity. In this review, we summarized emerging methodological approaches in the field of brain organoid technologies and their application to dissect disease mechanisms underlying an array of pediatric brain developmental disorders, with a particular focus on autism spectrum disorders and epileptic encephalopathies.